Pengaruh Kualitas Layanan terhadap Kepuasan Pelanggan Perumda Giri Tirta Cabang Cerme Kabupaten Gresik (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to examine the influence of service quality dimensions—Tangible, Reliability, Responsiveness, Assurance, and Empathy—on customer satisfaction at Perumda Giri Tirta Cabang Cerme, Gresik Regency. A quantitative research approach was employed with a sample of 180 customers. Data were analyzed using classical assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression, t-tests (partial effects), and an F-test (simultaneous effects) with the aid of SPSS 25. The results indicate that, partially, the variables of Tangible (β = 0.131; p = 0.022), Reliability (β = 0.131; p = 0.040), and Responsiveness (β = 0.352; p = 0.000) significantly influence customer satisfaction. This suggests that adequate physical facilities, accurate and consistent service delivery, and prompt response to complaints are key drivers of satisfaction. Conversely, Assurance (β = 0.020; p = 0.726) and Empathy (β = 0.105; p = 0.620) do not exert statistically significant individual effects, likely due to the monopolistic nature of water supply services, where customers prioritize water availability and quality over interpersonal interactions or service guarantees. However, the F-test results demonstrate that collectively, all five dimensions have a highly significant effect on customer satisfaction (F = 72.570; p = 0.000). This finding confirms that although some dimensions may appear less dominant individually, they collectively contribute holistically to forming a satisfying service experience. This study provides empirical contribution to public service management literature, particularly in the context of regional utilities, and recommends that Perumda Giri Tirta Cabang Cerme prioritize infrastructure enhancement, maintain distribution reliability, and accelerate complaint resolution as core strategies to improve service quality and customer satisfaction.